Pengaruh Motivasi terhadap Performance Mahasiswa Akuntansi dengan Effort sebagai Variabel Mediasi - Eko Arief Sudaryono; . Baratha (Jurnal Akuntansi dan Bisnis, 2004)
Motivation is the important determinant of individual performance. With the high motivation to study, student is hoped doing the best effort to obtain the optimum performance. This study aimed to understand whether the motivation influences the students’ performance, with the effort as intervening variable. This study also aimed to test the influence of motivation to the students’ effort. Using under graduate students of Economics Faculty of Sebelas Maret University that studying Intermediate Accounting (II) in January to July 2002, F-test output show that motivation and effort influence the performance simultaneously and significantly. Determinant Coefficient (R2) value (0,204) indicates that motivation and effort explain only 20,4% of performance, and the remainder (79,6%) explained by other factors. The output of path analysis indicates that motivation influences the performance of accounting student with effort as intervening variable, and motivation influences the effort significantly. Its indicated by motivation ® effort path coefficient (0,318) and effort ® performance path coefficient (0,422), more than motivation ® performance path coefficient (0,050).